Innovations in the agriculture of Central America: progress, institutional capacity and policy needs - Pomareda, Carlos (International Center for Tropical Agriculture, 2016)
This paper has been prepared under the guidelines provided by the TAP Secretariat at the FAO, as a contribution to the TAP, an initiative of the G.20, which includes near 40 partners, facilitated by the FAO.